Disentangling the Holism of Intentional Systems From the Interactionism of Mechanistic Systems in Person-Oriented Research - Artur Nilsson (Journal for Person-Oriented Research, 2015)
A key assumption in the person-oriented approach is that a person must be understood as a complex, integrated system, represented by patterns of within-person variation rather than scores on separate variables. The term ‘system’ does, however, have multiple meanings, which are not clearly distinguished in the person-oriented literature. I try to disentangle causal interactionism, which describes the psychological consequences and functions of each component of the system as dependent upon its causal interaction with other system components, from content holism, which describes the system components as in part constituted by their relations to each other and the system as a whole. Although the terms ‘interactionism’ and ‘holism’ are often treated as combinable and interchangeable, causal interactionism and content holism pertain to distinct kinds of research problems. Causal interactionism construes the person in terms of the hierarchically structured mechanistic systems that underpin his or her attributes and shape them over time, and can be exemplified in terms of Magnusson’s developmental approach, whereas content holism is integral to our understanding of the person as an intentional system, whose mental states and actions are interweaved through principles of logic and rationality rather than material causality, and can be exemplified in terms of Stephenson’s Q-methodological approach.